Nickel(II) complex of polyhydroxybenzaldehyde N4-thiosemicarbazone exhibits anti-inflammatory activity by inhibiting NF-κB transactivation. - Hana Bashir Shawish (Public Library of Science (PLoS), 2014)
Background The biological properties of thiosemicarbazone have been widely reported. The incorporation of some transition metals such as Fe, Ni and Cu to thiosemicarbazone complexes is known to enhance its biological effects. In this study, we incorporated nickel(II) ions into thiosemicarbazone with N4-substitution groups H3L (H; H3L1, CH3; H3L2, C6H5; H3L3 and C2H5; H3L4) and examined its potential anti-inflammatory activity. Methodology/principal findings Four ligands (1-4) and their respective nickel-containing complexes (5-8) were synthesized and characterized. The compounds synthesized were tested for their effects on NF-κB nuclear translocation, pro-inflammatory cytokines secretion and NF-κB transactivation activity. The active compound was further evaluated on its ability to suppress carrageenan-induced acute inflammation in vivo. A potential binding target of the active compound was also predicted by molecular docking analysis. Conclusions/significance Among all synthesized compounds tested, we found that complex [Ni(H2L1)(PPh3)]Cl (5) (complex 5), potently inhibited IκBα degradation and NF-κB p65 nuclear translocation in LPS-stimulated RAW264.7 cells as well as TNFα-stimulated HeLa S3 cells. In addition, complex 5 significantly down-regulated LPS- or TNFα-induced transcription of NF-κB target genes, including genes that encode the pro-inflammatory cytokines TNFα, IFNβ and IL6. Luciferase reporter assays confirmed that complex 5 inhibited the transactivation activity of NF-κB. Furthermore, the anti-inflammatory effect of complex 5 was also supported by its suppressive effect on carrageenan-induced paw edema formation in wild type C57BL/6 mice. Interestingly, molecular docking study showed that complex 5 potentially interact with the active site of IKKβ. Taken together, we suggest complex 5 as a novel NF-κB inhibitor with potent anti-inflammatory effects.